Molecular compatibility analysis between proteins and their inhibitors: a case study in the formulation of the monoclonal antibody 4trp: Análisis de la compatibilidad molecular entre proteínas y sus inhibidores: un estudio de caso en la formulación del anticuerpo monoclonal 4trp (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
The incorporation of protease inhibitors (saquinavir, ritonavir, indinavir, nelfinavir, amprenavir, and lopinavir) into antiretroviral therapy has significantly reduced the morbidity and mortality associated with AIDS. These non-peptidic compounds potently and selectively inhibit HIV-1 protease. Therefore, an affinity study was conducted between the protease enzyme and each of its inhibitors by their binding energy using molecular docking to determine which inhibitor exhibits the highest binding affinity. Additionally, hydrogen bond interactions between the receptor and each ligand were analyzed to evaluate their correlation. From another perspective, this study examines the synthesis of the monoclonal antibody 4BINDING AFFINITY (IgG2a, derived from a murine IgG3 subclass antibody. Several mutations were introduced into the protein structure, replacing residues identified as high-risk for deamidation reactions. The analysis aimed to compare structural modifications to identify those that minimize aggregation risk. A quality assessment of the mutated product was conducted, supporting the stability improvements observed.